Comparison of Dimensional Stability and Surface Detail Reproduction of Silicone Based Impression Materials - Riwaj Karki; Dipendra Naulakha (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 68-73